STIMULASI PERKEMBANGAN MOTORIK KASAR TERHADAP PEMBELAJARAN JASMANI ANAK - zulnadila, zulnadila; Sumaryanti, Sumaryanti; Suhartini, Bernadeta; Budiyanti, Eka Swasta (Jurnal Tunas Pendidikan, 2024)
Education has a major role in the formation of a person's personality, playing an important role in shaping human character in accordance with applicable norms. Through physical education, students are socialized into physical activities, including sports skills. These physical activities provide opportunities for students to engage directly in a variety of learning experiences, including motor stimulation and the development of sports skills. This type of research uses a literature study in writing reviewing literature through various journals, theoretical references that are relevant to the research topic. The impact of gross motor development stimulation on children's physical learning is examined in this study. Various studies show the importance of targeted and quality stimulation, both through physical education and other stimulating activities, in improving children's motor development at various levels.